2021
DOI: 10.1002/cam4.4370
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles as a new hope for diagnosis and therapeutic intervention for hepatocellular carcinoma

Abstract: Liver cancer is the sixth most common cancer found in cancer patients worldwide 1 and 90% of liver cancer is hepatocellular carcinoma (HCC). 2 Chronic liver injury from infection (hepatitis B or C viruses), chronic alcoholic intake, and fatty liver are well-known risk factors for hepatocarcinogenesis. 3 The treatments for HCC are dependent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 90 publications
(233 reference statements)
0
11
0
Order By: Relevance
“…Moreover, the obtained data revealed that HCC cell-derived EVs could deliver LOXL4 into macrophages to promote immunosuppression in HCC cells. It has been reported that EVs serve as a potential source of biomarkers for HCC by delivering biomolecular cargo, including nucleic acid, lipids, and proteins 7 . Tumor cells–derived exosomes induce HCC immune escape by carrying cancer‐derived molecules 9,35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the obtained data revealed that HCC cell-derived EVs could deliver LOXL4 into macrophages to promote immunosuppression in HCC cells. It has been reported that EVs serve as a potential source of biomarkers for HCC by delivering biomolecular cargo, including nucleic acid, lipids, and proteins 7 . Tumor cells–derived exosomes induce HCC immune escape by carrying cancer‐derived molecules 9,35 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that extracellular vesicles (EVs) are implicated in the progression of HCC 6 . EVs significantly affect cell‐to‐cell communication by delivering molecules such as protein, mRNA, microRNA (miRNA), and long noncoding RNA 7 . It is interesting to note that HCC-derived exosomes can regulate immune cells during the progression of tumors 8,9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HCC is a lethal abdominal malignancy with few effective intervention strategies in its late stages [ 37 , 38 ]. The advent of immunotherapy, represented by ICB therapy, created novel opportunities for advanced HCC patients [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…60 EVs are promising biomarkers for early HCC detection evidenced by the increasing number of studies published. [61][62][63][64][65] As key mediators of intercellular communication EVs are present in the circulation at early stages of disease. 66,67 One study in 158 patients with HCC that a 10-gene molecular signature had 94% sensitivity and 89% specificity in detecting early HCC.…”
Section: Data On Clinical Applications Of Liquid Biopsy For Hcc Early...mentioning
confidence: 99%